A kind of adhesive film
The UV adhesive film is solved by combining graft polymerization of modified polyester resins with end-hydroxyl polyester resins, isocyanoethyl methacrylate and (meth)acrylate monomers, with tackifying resins and photocuring agents. The volume shrinkage and deformation problems during aging improve cohesive strength and adhesion, and achieve efficient film adhesion and durability.
Patent Information
- Application Number
- CN202411096436.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-12
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-08-12
AI Technical Summary
The existing UV adhesive films have problems with large volume shrinkage, warping and deformation during the aging process, which affects the product's adhesion and processing process stability.
The modified polyester resin obtained by graft polymerization of end-hydroxyl polyester resin, isocyanoethyl methacrylate and (meth)acrylate monomers were used, and mixed with tackifying resin and photocuring agent to add catalyst and free radicals. Polymerization initiator, a UV adhesive film with high cohesion strength was prepared.
It improves the cohesive strength of the adhesive film and the adhesion of PET substrate, extends the initial peeling force, facilitates removal, enhances the bonding strength, improves long-term use resistance, and is suitable for the bonding of flat electronic glasses.
Smart Images

Figure CN118638483B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of tackifying adhesive films, and in particular to a tackifying adhesive film. Background Art
[0002] With the development of display technology, the tape needs to have strong adhesion and reworkability. For example, in the OLED module section, a high-viscosity support film is bonded to the OLED screen PI, but due to the excessive viscosity, poor bonding will result in a certain yield loss. Currently, a tackifying tape is used, such as thermal tackifying, UV tackifying, etc. The characteristics of this type of tape are low initial viscosity and good rework performance. After tackifying, the viscosity becomes stronger and provides strong adhesion. The tackifying tape is prepared by coating the tackifying glue on the surface of the substrate to replace the solid-gas interface of the original substrate, and then drying, pressing and aging.
[0003] However, the current UV adhesive film has a large volume shrinkage caused by the UV cross-linking reaction, which causes warping and deformation of the product during the aging process. At the same time, the cross-linking density is too high, which will affect the adhesion of the product and the stability of the subsequent processing parameters. Summary of the invention
[0004] In view of the above-mentioned shortcomings of the prior art, the present invention provides an adhesion-enhancing adhesive film, which can effectively solve the above-mentioned problems of the prior art.
[0005] Technical Solution
[0006] To achieve the above objectives, the present invention is implemented through the following technical solutions:
[0007] The invention provides a tackifying adhesive film, which comprises a substrate layer and a UV tackifying adhesive layer coated on the substrate layer. The UV tackifying adhesive layer is prepared by using a modified polyester resin obtained by graft polymerization of terminal hydroxyl polyester resin, isocyanoethyl methacrylate and (meth)acrylate monomer as a main resin, and mixing it with a tackifying resin and a light curing agent.
[0008] Furthermore, a catalyst and a free radical polymerization initiator are added during the preparation of the modified polyester resin, wherein the catalyst is dibutyltin dilaurate.
[0009] Furthermore, the specific preparation steps of the modified polyester resin are as follows:
[0010] (1) Add hydroxyl-terminated polyester resin, isocyanatoethyl methacrylate (MOI), dibutyltin dilaurate, and organic solvent into a reactor, mix, heat to 50-70°C, and react at this temperature for 4-6 hours;
[0011] (2) raising the temperature to 70-90° C., and then slowly adding a mixture of (meth)acrylate monomer and free radical polymerization initiator into the reactor, and performing graft polymerization reaction for 3-5 hours to obtain a modified polyester resin solution;
[0012] Among them, the above reactions are all carried out under nitrogen protection.
[0013] Furthermore, the specific preparation steps of the modified polyester resin are as follows:
[0014] (1) Add 60-90 parts by weight of hydroxyl-terminated polyester resin, 0.5-3 parts by weight of isocyanatoethyl methacrylate (MOI), 0.01-0.10 parts by weight of dibutyltin dilaurate, and 100 parts by weight of organic solvent into a reactor, heat the reactor to 60°C, and react at the same temperature for 5 hours;
[0015] (2) raising the temperature to 80° C., and then slowly adding a mixture of 7 to 39.5 parts of (meth)acrylate monomer and 0.1 to 2 parts of a free radical polymerization initiator into the reactor, and performing a graft polymerization reaction for 4 hours to obtain a modified polyester resin solution;
[0016] Wherein, the above reactions are all carried out under nitrogen protection;
[0017] In step (1), the organic solvent is one or more of ethyl acetate, toluene, acetone, butanone and isopropanol mixed in any proportion;
[0018] The (meth)acrylate monomer includes at least one or more of (meth)acrylate alkyl esters, aromatic ring-containing (meth)acrylate esters, (meth)acrylate hydroxyalkyl esters, (meth)acrylate glycidyl esters, (meth)acrylate alkoxyalkyl esters, (meth)acrylate allyl alkyl esters and multifunctional (meth)acrylate esters;
[0019] Preferably, the (meth)acrylate monomer includes at least one or more of methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, dodecyl (meth)acrylate, stearyl (meth)acrylate and behenyl (meth)acrylate;
[0020] Preferably, the (meth)acrylate monomer includes at least one or more of ethyl (meth)acrylate, butyl (meth)acrylate and 2-ethylhexyl (meth)acrylate, and most preferably, the (meth)acrylate monomer is butyl (meth)acrylate.
[0021] In this specification, (meth)acrylate refers to acrylate and / or methacrylate;
[0022] The free radical polymerization initiator is selected from at least one or two of benzoyl peroxide and azobisisobutyronitrile.
[0023] Preferably, the specific preparation steps of the modified polyester resin are as follows:
[0024] (1) Add 75 parts by weight of hydroxyl-terminated polyester resin, 2.18 parts of isocyanatoethyl methacrylate (MOI), 0.075 parts of dibutyltin dilaurate, and 100 parts of an organic solvent into a reactor, mix, heat to 60° C., and react at this temperature for 5 hours;
[0025] (2) raising the temperature to 80° C., and then slowly adding a mixture of 20 parts of (meth)acrylate monomer and 1 part of free radical polymerization initiator into the reactor, and performing graft polymerization reaction for 4 hours to obtain a modified polyester resin solution;
[0026] Among them, the above reactions are all carried out under nitrogen protection.
[0027] Furthermore, the tackifying resin is hydrogenated rosin glycerol ester.
[0028] Further, the photocuring agent is one or more of 1,6-hexanediol diacrylate, 1,6-hexanediol dimethacrylate, polyethylene glycol diacrylate, polypropylene glycol diacrylate, trimethylolpropane triacrylate, and trimethylolpropane trimethacrylate;
[0029] Preferably, the photocuring agent is 1,6-hexanediol diacrylate (HDDA) and trimethylolpropane triacrylate, and the weight ratio of 1,6-hexanediol diacrylate (HDDA) to trimethylolpropane triacrylate is 3:1.
[0030] Furthermore, the cross-linking agent is a polyisocyanate curing agent or a carboxyl cross-linking agent that can react with a hydroxyl group or a carboxyl group; the polyisocyanate curing agent is a compound containing two or more isocyanate groups in one molecule, and is one of an aromatic polyisocyanate or an aliphatic polyisocyanate; the carboxyl cross-linking agent is one or more of a polyfunctional aziridine (trimethylolpropane-tris[3-(2-methylaziridinyl) propionate], SC-100) and a tetrafunctional epoxy resin (N,N,N',N'-tetraglycidyl-m-xylene diamine, GA-240).
[0031] Furthermore, the initiator is one or more free radical initiators such as 1-hydroxycyclohexyl phenyl ketone, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, 2,4,6-trimethylbenzoylphenylphosphonic acid ethyl ester, phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butanone and 2-dimethylamino-2-benzyl-1-(4-piperidinylphenyl)-1-butanone.
[0032] The auxiliary agent includes a stabilizer, which is a phenolic compound or a quinone compound, and the stabilizer is one or a mixture of 4-methoxyphenol, 4-methoxynaphthol, tert-butylhydroquinone, dibutylhydroxytoluene, benzoquinone, and 1,4-naphthoquinone.
[0033] Furthermore, the UV tackifying adhesive layer comprises, by weight, 30-50 parts of modified polyester resin, 10-30 parts of photocuring agent, 5-10 parts of tackifying resin, 0.2-3 parts of crosslinking agent, 0.5-2 parts of initiator and 0.01-0.1 parts of auxiliary agent.
[0034] Furthermore, the UV tackifying adhesive layer comprises, by weight, 35-45 parts of modified polyester resin, 15-25 parts of photocuring agent, 6.5-9 parts of tackifying resin, 0.5-1.5 parts of crosslinking agent, 0.5-1.5 parts of initiator and 0.01-0.1 parts of auxiliary agent.
[0035] A method for preparing an adhesive film comprises the following steps:
[0036] (1) First, the modified polyester resin and the light curing agent are added to the solvent and stirred to obtain a mixed solution, and then the tackifying resin, the cross-linking agent, the initiator and the auxiliary agent are added to the mixed solution and stirred to obtain a tackifying adhesive;
[0037] (2) applying the tackifier obtained in step (1) onto the surface of the substrate layer, heating at 50-130° C. for 3-5 min to dry and solidify, attaching a release film, and aging at 40-50° C. for 48 h-72 h to obtain a UV tackifier film;
[0038] In step (1), the solvent is one or more of ethyl acetate, toluene, acetone, butanone and isopropanol mixed in any proportion.
[0039] The release film layer has a thickness of 25-100 μm, and the release film layer is a silicone release film or a non-silicone release film; preferably, the release film layer is PET.
[0040] The thickness of the UV adhesion enhancing adhesive layer is 5 μm to 100 μm;
[0041] The substrate layer is one of PET, PO / PP / PE, PI or PEN, and the thickness of the substrate layer is 5 μm to 300 μm. Preferably, the substrate layer is PET.
[0042] The substrate layer is PET (polyethylene terephthalate), PO / PP / PE (polyolefin film), PI (polyimide film) or PEN (polyethylene naphthalate), and the thickness of the substrate layer is 5 μm to 300 μm.
[0043] Beneficial Effects
[0044] Compared with the known prior art, the technical solution provided by the present invention has the following beneficial effects:
[0045] (1) The modified polyester resin obtained by graft polymerization of terminal hydroxyl polyester resin, butyl methacrylate and isocyanoethyl methacrylate is used as the main resin, and mixed with a tackifying resin and a light curing agent to prepare a tackifying film, which has high cohesive strength and good adhesion to the PET substrate. Before the UV tackifying reaction, the initial peeling force will not increase significantly with the extension of the placement time, so it can be easily removed. Removing the tape will not cause damage to the adhered object and cause pollution such as residual adhesive. After the UV tackifying reaction, the modified polyester resin can improve the bonding strength between the tape and the adhered object.
[0046] (2) The adhesive film of the present invention has a high initial bonding strength to the substrate, which can ensure the positioning effect; after positioning, under a certain UV irradiation, the adhesive film can be further cross-linked and hardened. After hardening, the adhesive ability of the adhesive film to the substrate is greatly improved. At the same time, the modulus and strength of the adhesive film are also greatly improved, which not only ensures the bonding effect but also improves the long-term use tolerance. It can be well applied to the bonding of flat electronic glass.
[0047] (3) In the present invention, the polyester resin and the PET used as the substrate are both polyester materials. Therefore, the prepared UV adhesive layer has a high cohesive strength and good adhesion to the PET substrate. The UV adhesive layer obtained by modifying the polyester resin will not have an obvious increase in initial peeling force as the placement time increases before the UV adhesive reaction, so it can be easily removed. Removing the tape will not cause damage to the adhered object or cause pollution such as residual adhesive. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the prior art descriptions are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0049] Figure 1 It is a schematic diagram of the structure of the UV adhesion-enhancing adhesive film of the present invention.
[0050] The numbers in the figure represent:
[0051] 1-substrate layer, 2-UV adhesion-enhancing adhesive layer, 3-release film layer. DETAILED DESCRIPTION
[0052] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0053] The present invention will be further described below in conjunction with the embodiments.
[0054] The sources and models of raw materials in the synthesis experiments, embodiments and comparative examples are as follows:
[0055] Hydrogenated rosin glycerol ester, Shenzhen Jitian Chemical Co., Ltd.;
[0056] 1,6-Hexanediol diacrylate (HDDA), Changxing Chemical Materials Co., Ltd.;
[0057] Isocyanoethyl methacrylate (MOI), Showa Denko, Japan;
[0058] Hydroxyl-terminated polyester resin, model GK680 from Toyobo Co., Ltd., Japan (hydroxyl value: 21 mg / g KOH);
[0059] Carboxyl-terminated polyester resin, Anhui Shenjian SJ6B;
[0060] Rosin phenolic resin, Arakawa Chemical Co., Ltd. model: T-803L.
[0061] 1. Synthesis of modified polyester resin
[0062] Synthesis experiment 1:
[0063] Under nitrogen protection, 75 parts of terminal hydroxyl polyester resin, 100 parts of organic solvent, 2.18 parts of isocyanoethyl methacrylate, and 0.075 parts of dibutyltin dilaurate catalyst were added to the reactor by weight and mixed, and the temperature was raised to 60°C for reaction for 5 hours; then the temperature was raised to 80°C, and then a mixture of 20 parts of (meth)acrylate monomer and 1 part of free radical polymerization initiator was slowly added to the reaction container, and the graft polymerization reaction was carried out for 4 hours to obtain modified polyester resin GX1.
[0064] Wherein, the (meth)acrylate monomer is butyl methacrylate;
[0065] Free radical polymerization initiator: benzoyl peroxide and azobisisobutyronitrile, and the weight ratio is 2:1;
[0066] The organic solvent used was ethyl acetate.
[0067] Synthesis experiment 2:
[0068] Compared with the synthesis experiment 1, the only difference is that the hydroxyl-terminated polyester resin is replaced by a carboxyl-terminated polyester resin.
[0069] Modified polyester resin GX2 was prepared through synthesis experiment 2.
[0070] Synthesis experiment 3:
[0071] Compared with the synthesis experiment 1, the only difference is that: isocyanoethyl methacrylate is not added;
[0072] Modified polyester resin GX3 was prepared through synthesis experiment 3.
[0073] (II) Preparation of adhesion-enhancing film
[0074] Embodiment 1:
[0075] A tackifying adhesive film, comprising the following preparation steps:
[0076] (1) First, 40 parts of modified polyester resin and 20 parts of photocuring agent were added to 150 parts of ethyl acetate by weight, and the mixture was stirred to obtain a mixed solution. Then, 7.5 parts of tackifying resin, 0.75 parts of crosslinking agent, 1 part of initiator and 0.05 parts of auxiliary agent were added to the mixed solution, and the mixture was stirred for 1 hour to obtain a tackifying adhesive.
[0077] (2) coating the tackifier obtained in step (1) onto the surface of a 75 μm thick transparent PET substrate film layer, heating at 90° C. for 4 min to dry and solidify, laminating a 50 μm thick transparent PET release film, and aging at 45° C. for 60 h to obtain a UV tackifier film;
[0078] Among them, the thickness of the adhesion-enhancing adhesive layer is 18 μm;
[0079] The modified polyester resin adopts GX1;
[0080] The photocuring agent is 1,6-hexanediol diacrylate (HDDA) and trimethylolpropane triacrylate, and the weight ratio of 1,6-hexanediol diacrylate (HDDA) to trimethylolpropane triacrylate is 3:1;
[0081] The tackifying resin is hydrogenated rosin glycerol ester;
[0082] The cross-linking agent is a multifunctional aziridine (trimethylolpropane-tris[3-(2-methylaziridinyl) propionate], SC-100);
[0083] The initiator is 2,4,6-trimethylbenzoyldiphenoxyphosphine;
[0084] The auxiliary agent is tert-butylhydroquinone.
[0085] Embodiment 2:
[0086] A tackifying adhesive film, comprising the following preparation steps:
[0087] (1) First, 35 parts of modified polyester resin and 25 parts of photocuring agent were added to 150 parts of ethyl acetate and stirred to obtain a mixed solution, and then 6.5 parts of tackifying resin, 1.5 parts of crosslinking agent, 0.5 parts of initiator and 0.05 parts of auxiliary agent were added to the mixed solution, and stirred for 1 hour to obtain a tackifying adhesive;
[0088] (2) coating the tackifier obtained in step (1) onto the surface of a 75 μm thick transparent PET substrate film layer, heating at 90° C. for 4 min to dry and solidify, laminating a 50 μm thick transparent PET release film, and aging at 45° C. for 60 h to obtain a UV tackifier film;
[0089] Among them, the thickness of the adhesion-enhancing adhesive layer is 18 μm;
[0090] The modified polyester resin adopts GX1;
[0091] The photocuring agent is 1,6-hexanediol diacrylate (HDDA) and trimethylolpropane triacrylate, and the weight ratio of 1,6-hexanediol diacrylate (HDDA) to trimethylolpropane triacrylate is 3:1;
[0092] The tackifying resin is hydrogenated rosin glycerol ester;
[0093] The cross-linking agent is a multifunctional aziridine (trimethylolpropane-tris[3-(2-methylaziridinyl) propionate], SC-100);
[0094] The initiator is 2,4,6-trimethylbenzoyldiphenoxyphosphine;
[0095] The auxiliary agent is tert-butylhydroquinone.
[0096] Embodiment 3:
[0097] A tackifying adhesive film, comprising the following preparation steps:
[0098] (1) First, 45 parts of modified polyester resin and 15 parts of photocuring agent were added to 150 parts of ethyl acetate and stirred to obtain a mixed solution, and then 9 parts of tackifying resin, 0.5 parts of crosslinking agent, 0.9 parts of initiator and 0.03 parts of auxiliary agent were added to the mixed solution, and stirred for 1 hour to obtain a tackifying adhesive;
[0099] (2) coating the tackifier obtained in step (1) onto the surface of a 75 μm thick transparent PET substrate film layer, heating at 90° C. for 4 min to dry and solidify, laminating a 50 μm thick transparent PET release film, and aging at 45° C. for 60 h to obtain a UV tackifier film;
[0100] Among them, the thickness of the adhesion-enhancing adhesive layer is 18 μm;
[0101] The modified polyester resin adopts GX1;
[0102] The photocuring agent is 1,6-hexanediol diacrylate (HDDA) and trimethylolpropane triacrylate, and the weight ratio of 1,6-hexanediol diacrylate (HDDA) to trimethylolpropane triacrylate is 3:1;
[0103] The tackifying resin is hydrogenated rosin glycerol ester;
[0104] The cross-linking agent is a multifunctional aziridine (trimethylolpropane-tris[3-(2-methylaziridinyl) propionate], SC-100);
[0105] The initiator is 2,4,6-trimethylbenzoyldiphenoxyphosphine;
[0106] The auxiliary agent is tert-butylhydroquinone.
[0107] Comparative Example 1:
[0108] The only difference from Example 1 is that the modified polyester resin used is GX2.
[0109] Comparative Example 2:
[0110] The only difference from Example 1 is that the modified polyester resin used is GX3.
[0111] Comparative Example 3:
[0112] The only difference from Example 1 is that no tackifying resin is added.
[0113] Comparative Example 4:
[0114] The only difference from Example 1 is that the tackifying resin is rosin phenolic resin (model: T-803L, manufacturer: Arakawa Chemical Co., Ltd.).
[0115] Comparative Example 5:
[0116] The only difference from Example 1 is that the photocuring agent is 1,6-hexanediol diacrylate (HDDA).
[0117] Comparative Example 6:
[0118] The only difference from Example 1 is that the photocuring agent is trimethylolpropane triacrylate.
[0119] (III) Performance testing
[0120] The UV tackifying adhesive films prepared in the above examples and comparative examples were respectively tested for pre- and post-UV peeling force, reliability aging performance under different conditions, and aging shrinkage rate, and the testing methods are as follows.
[0121] (1) Initial 180° peel force test: Cut the samples of each embodiment into 25 mm wide and 250 mm long strips, remove the release film and laminate them onto a 75 μm*50 mm*150 mm PI film. Clamp the ends of each strip onto the tensile fixture of a tensile testing machine and perform 180° peeling at a speed of 300 mm / min. Calculate the average value of 5 sets of data.
[0122] (2) UV adhesion 180° peel strength test: The samples of each embodiment were cut into 25 mm wide and 250 mm long, the release film was removed and the samples were laminated on a 75 μm*50 mm*150 mm PI film. A 365 nm LED light source was used to irradiate the samples, and the light energy was 4000 mj / cm 2 (200mw / cm 2 The light intensity was irradiated for 20 seconds), the end of each strip was clamped on the tensile fixture of the tensile testing machine, and 180° peeling was performed at a speed of 300 mm / min. Five groups of data were tested and the average value was calculated.
[0123] (3) Substrate adhesion test: According to JIS K 5600 standard, 10×10 squares were drawn at 1 mm intervals on the adhesive layer of the UV tackifying tape sample prepared above, and after being covered with transparent tape (3M, Scotch Tape), they were quickly peeled off at an angle of 90°, and the number of squares that were not peeled off was recorded. The results were judged according to the following standards:
[0124] ○:100 / 100
[0125] △: 99 / 100~80 / 100
[0126] ×: 0 / 100~79 / 100
[0127] (4) Double 85 aging test: Cut the samples of each embodiment into 50 mm wide and 150 mm long, remove the release film and laminate them on a 75 μm*100 mm*200 mm PI film. Use a 365 nm LED light source to irradiate the samples, and the light energy is 4000 mj / cm 2 (200mw / cm 2 The samples were aged for 240 hours in a constant temperature and humidity chamber at 85°C and 85% relative humidity, and the presence of bubbles, delamination, fractures and other defects between the samples and the PI film was observed. If none of the above defects exists, it is "qualified", and if any of them exists, it is "unqualified".
[0128] 60℃ / 90% aging test: Cut the samples of each embodiment into 50mm width and 150mm length, remove the release film and laminate them on 75μm*100mm*200mm PI film, and irradiate the samples with 365nm LED light source, with the light energy of 4000mj / cm 2 (200mw / cm 2 The samples were aged for 240 hours in a constant temperature and humidity chamber at 60°C and 90% relative humidity to observe whether there were bubbles, delamination, fractures and other defects between the samples and the PI film. If there were no such defects, it was "qualified". If there were any of them, it was "unqualified".
[0129] -40℃ aging test: Cut the samples of each embodiment into 50mm width and 150mm length, remove the release film and laminate them on 75μm*100mm*200mm PI film, and irradiate the samples with 365nm LED light source, with the light energy of 4000mj / cm 2 (200mw / cm 2 The samples were placed in a constant temperature and humidity chamber at -40°C and relative humidity for 240 hours to observe whether there were bubbles, delamination, fractures and other defects between the samples and the PI film. If there were no such defects, it was "qualified". If there were any of them, it was "unqualified".
[0130] Thermal shock aging test: Cut the samples of each embodiment into 50 mm wide and 150 mm long, remove the release film and laminate them on a 75 μm*100 mm*200 mm PI film. Use a 365 nm LED light source to irradiate the samples, and the light energy is 4000 mj / cm 2 (200mw / cm 2 The samples were placed in a -40℃~85℃ cycle / 30min hot and cold shock box for aging for 100 cycles, and the presence of bubbles, delamination, fractures and other defects between the samples and the PI film was observed. If none of the above defects exists, it is "qualified", and if any of them exists, it is "unqualified".
[0131] Aging shrinkage test: Cut the samples of each embodiment into A4 sample size, remove the release film and stick it on a 250mm×330mm glass plate, and irradiate the sample with a 365nm LED light source with a light energy of 4000mj / cm 2 (200mw / cm 2 The sample was placed in a constant temperature and humidity chamber at 85°C and 85% relative humidity for 240 hours, then taken out and cooled to room temperature, and the perimeter of the sample was tested again using the microscope. The aging shrinkage formula is:
[0132] .
[0133] The specific test results are shown in the following table:
[0134]
[0135] Through the examples and comparative examples, it can be seen that the tackifying film prepared by using a modified polyester resin obtained by graft polymerization of terminal hydroxyl polyester resin, butyl methacrylate and isocyanoethyl methacrylate as the main resin and mixing it with a tackifying resin and a light curing agent has high cohesive strength and good PET substrate adhesion. Before the UV tackifying reaction, the initial peeling force will not increase significantly with the extension of the placement time, so it can be easily removed, and the removal of the tape will not cause damage to the adhered object and cause pollution such as residual adhesive. After the UV tackifying reaction, the modified polyester resin can improve the bonding strength between the tape and the adhered object, and the UV tackifying 180° peeling force is greater than 1800 g / 25mm.
[0136] The adhesive film of the present invention has a high initial bonding strength to the substrate, which can ensure the positioning effect; after positioning, under a certain UV irradiation, the adhesive film can be further cross-linked and hardened, and the adhesive ability of the adhesive film to the substrate is greatly improved after hardening, which not only ensures the bonding effect but also improves the long-term use tolerance, and it can be well applied to the bonding of flat electronic glass.
[0137] In the present invention, the polyester resin and the PET used as the substrate are both polyester materials, and therefore, the prepared UV tackifying adhesive layer has high cohesive strength and good adhesion to the PET substrate. The UV adhesive layer obtained by modifying the polyester resin will not have an obvious increase in initial peeling force as the placement time increases before the UV tackifying reaction, so that it can be easily removed, and the removal of the tape will not cause damage to the adhered object or pollution such as residual adhesive.
[0138] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the protection scope of the technical solutions of the embodiments of the present invention.
Claims
1. A tackifying adhesive film, characterized in that: The UV adhesive layer comprises a substrate layer and a UV adhesive layer coated on the substrate layer, wherein the UV adhesive layer is prepared by using a modified polyester resin obtained by graft polymerization of a terminal hydroxyl polyester resin, isocyanoethyl methacrylate and (meth)acrylate monomer as a main resin, and mixing with an adhesive resin, a photocuring agent, a crosslinking agent, an initiator and an auxiliary agent; The tackifying resin is hydrogenated rosin glycerol ester; The photocuring agent is 1,6-hexanediol diacrylate (HDDA) and trimethylolpropane triacrylate; The cross-linking agent is a carboxyl cross-linking agent; In parts by weight, the UV tackifying adhesive layer comprises 30-50 parts of modified polyester resin, 10-30 parts of photocuring agent, 5-10 parts of tackifying resin, 0.2-3 parts of crosslinking agent, 0.5-2 parts of initiator and 0.01-0.1 parts of auxiliary agent.
2. The adhesion-promoting adhesive film according to claim 1, characterized in that: A catalyst and a free radical polymerization initiator are also added during the preparation of the modified polyester resin, wherein the catalyst is dibutyltin dilaurate.
3. The adhesion-promoting adhesive film according to claim 2, characterized in that: The specific preparation steps of the modified polyester resin are as follows: (1) adding hydroxyl-terminated polyester resin, isocyanoethyl methacrylate, dibutyltin dilaurate, and an organic solvent into a reactor, heating the reactor to 50-70° C., and reacting the mixture at the temperature for 4-6 hours; (2) raising the temperature to 70-90° C., and then slowly adding a mixture of (meth)acrylate monomer and free radical polymerization initiator into the reactor, and performing graft polymerization reaction for 3-5 hours to obtain a modified polyester resin; Among them, the above reactions are all carried out under nitrogen protection.
4. The adhesion-promoting adhesive film according to claim 2, characterized in that: The specific preparation steps of the modified polyester resin are as follows: (1) Add 60-90 parts by weight of hydroxyl-terminated polyester resin, 0.5-3 parts by weight of isocyanoethyl methacrylate, 0.01-0.10 parts by weight of dibutyltin dilaurate, and 100 parts by weight of organic solvent into a reactor, heat the mixture to 50-70° C., and react at the temperature for 4-6 hours; (2) raising the temperature to 70-90° C., and then slowly adding a mixture of 7-39.5 parts of (meth)acrylate monomer and 0.1-2 parts of free radical polymerization initiator into the reactor, and performing graft polymerization reaction for 3-5 hours to obtain a modified polyester resin; Wherein, the above reactions are all carried out under nitrogen protection; In step (1), the organic solvent is one or more of ethyl acetate, toluene, acetone, butanone and isopropanol mixed in any proportion.
5. The adhesion-promoting adhesive film according to claim 2, characterized in that: The (meth)acrylate monomer includes at least one or more of (meth)acrylate alkyl esters, aromatic ring-containing (meth)acrylates, (meth)acrylate hydroxyalkyl esters, (meth)acrylate glycidyl esters, (meth)acrylate alkoxyalkyl esters, (meth)acrylate allyl alkyl esters and multifunctional (meth)acrylates; the free radical polymerization initiator is selected from at least one or two of benzoyl peroxide and azobisisobutyronitrile.
6. The adhesion-promoting adhesive film according to claim 1, characterized in that: The carboxyl crosslinking agent is one or more of a multifunctional aziridine and a tetrafunctional epoxy resin; The initiator is one or more of 1-hydroxycyclohexyl phenyl ketone, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, 2,4,6-trimethylbenzoylphenylphosphonic acid ethyl ester, phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butanone and 2-dimethylamino-2-benzyl-1-(4-piperidinylphenyl)-1-butanone free radical initiators; The auxiliary agent includes a stabilizer, and the stabilizer is one or a mixture of 4-methoxyphenol, 4-methoxynaphthol, tert-butylhydroquinone, dibutylhydroxytoluene, benzoquinone, and 1,4-naphthoquinone.
7. A method for preparing a tackifying adhesive film as claimed in claim 1, characterized in that: It includes the following steps: (1) firstly adding the modified polyester resin and the light curing agent into the solvent and stirring and mixing to obtain a mixed solution, and then adding the tackifying resin, the crosslinking agent, the initiator and the auxiliary agent into the mixed solution and stirring evenly to obtain a tackifying adhesive; (2) coating the tackifier obtained in step (1) onto the surface of the substrate layer, heating at 50 to 130° C. for 3 to 5 min to dry and solidify, laminating the release film, and aging at 40 to 50° C. for 48 to 72 h to obtain a UV tackifier film; In step (1), the solvent is one or more of ethyl acetate, toluene, acetone, butanone and isopropanol mixed in any proportion.
